A Case of Fournier’s Gangrene Secondary to Varicella Zoster Virus in a 7-Year-Old Boy - Eimear Phoenix; Eoin O’Broin (Case Reports in Surgery)
A rare case of Fournier’s gangrene (FG) secondary to varicella-zoster virus (VZV) affecting the penis and scrotum of a 7-year-old boy is presented. To the authors’ knowledge, there are four cases of FG in children as a result of VZV reported to date. Our patient underwent a total of four surgical debridements and was reconstructed using a split-thickness skin graft (SSG). At 1-year post-reconstruction, his graft is robust, and he has no functional issues.